2020
DOI: 10.1093/jac/dkaa433
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology of carbapenemase-producingEscherichia colifrom duck farms in south-east coastal China

Abstract: Objectives To determine the dissemination and molecular characteristics of NDM-producing Escherichia coli strains from duck farms in south-east coastal China and their threats to human health. Methods A total of 232 NDM-producing E. coli were recovered from 1505 samples collected from 25 duck farms and their surrounding environments in five provinces in China. Resistance genes were confirmed using PCR. Genomic characteristics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 34 publications
6
24
0
Order By: Relevance
“…The fosfomycin-resistant E. coli were investigated by XbaI pulsed field electrophoresis (PFGE) and the locations of the fosfomycin resistance genes in the original isolates were determined by S1-PFGE mapping and Southern blot analysis, as described previously [19]. The PFGE patterns were analysed using a dendrogram of per cent similarity calculated with Dice coefficients using a cut-off of 80% [20]. The transferability of fosfomycin resistance genes was determined by the filter mating method using streptomycin-resistant E. coli C600 as a recipient strain, in accordance with a previous study [19].…”
Section: Molecular Analysis Of Fosfomycin-resistant E Colimentioning
confidence: 99%
“…The fosfomycin-resistant E. coli were investigated by XbaI pulsed field electrophoresis (PFGE) and the locations of the fosfomycin resistance genes in the original isolates were determined by S1-PFGE mapping and Southern blot analysis, as described previously [19]. The PFGE patterns were analysed using a dendrogram of per cent similarity calculated with Dice coefficients using a cut-off of 80% [20]. The transferability of fosfomycin resistance genes was determined by the filter mating method using streptomycin-resistant E. coli C600 as a recipient strain, in accordance with a previous study [19].…”
Section: Molecular Analysis Of Fosfomycin-resistant E Colimentioning
confidence: 99%
“…It is worthy to note that NDM-producing E. coli ST-1011 is prevalent in duck farms in southeast coastal China. 18 A previous study conducted in Lebanon found that ST1011 was one of the most widely identified clones associated with mcr-1-carrying E. coli and to the poultry sector. Our work further highlights the cooccurrence of NDM-9 and MCR-1 in E. coli ST1011 from https://doi.org/10.2147/IDR.S321732…”
Section: Resultsmentioning
confidence: 98%
“…ST156 and ST648 have been associated with the dissemination of bla NDM−5 and mcr-1 -producing E. coli isolates (Yang et al, 2016 ). The bla NDM -positive ST746 and ST354 prevalent in ducks and poultry have become a primary reservoir for bla NDM -positive ST746 E. coli isolates in China (Wang et al, 2021 ). Phylogenomic analysis found that two of the isolates that were recovered from a single sample possessed different genomes, which indicates the development of diversity in the population of bla NDM -positive E. coli isolates from ducks.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, mcr-1 , conferring resistance to the last-resort antibiotic colistin, was detected in 22 bla NDM -positive E. coli isolates. Some recent studies have reported that bla NDM and mcr-1 coproducing E. coli isolates were recovered from chicken (37/739, 5.0%), swine (16/105, 15.2%), and duck (11/92, 12.0%) farms (Kong et al, 2017 ; Wang et al, 2017 , 2021 ). There was also a high incidence of the co-harboring of mcr-1 and bla NDM in chickens (21/78, 26.9%) (Liu et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation